Strategi Pemasaran Destinasi Wisata Gunung Cilik Park Desa Wajakkidul Melalui Media Sosial Tiktok - Pramesti, Virgie Ayu; Ningrum, Cahya Kusuma; Ayuningtias, Mahardika Putri; Sari, Dewi Permata; Zahro, Alfani Putri; Diniati, Bintis Ti'anatud (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to determine how Gunung Cilik Park tourist destination marketing strategies utilize TikTok social media as a marketing tool. This study was conducted at Gunung Cilik Park tourist destination, Wajakkidul Village, Boyolangu Subdistrict, Tulungagung Regency. This study used a field study method with a qualitative approach. The qualitative approach collects data through interviews and relevant documents as supplementary materials. The results of this study indicate that the marketing strategies implemented by Gunung Cilik Park as a tourist destination are still not optimal. The strategies currently in place rely solely on word of mouth and personal posts from visitors themselves. This approach is deemed insufficiently effective in the marketing process. A solution to address this challenge could involve promoting the destination through social media platforms like TikTok to enhance branding and attract more visitors to Gunung Cilik Park.